2008
DOI: 10.1210/en.2008-0205
|View full text |Cite
|
Sign up to set email alerts
|

Sevelamer Restores Bone Volume and Improves Bone Microarchitecture and Strength in Aged Ovariectomized Rats

Abstract: Sevelamer hydrochloride, a noncalcium phosphate binder, has been shown to reduce coronary artery and aortic calcification, and to improve trabecular bone mineral density in hemodialysis patients with chronic kidney disease. Here, we examined whether sevelamer given orally for 12 wk with normal food could restore bone volume (BV) and strength in aged ovariectomized (OVX) rats starting at 4 wk after OVX. Dual-energy x-ray absorptiometry, microcomputerized tomography, and bone histomorphometry analyses showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…33,34 In the ovariectomized rat model of high turnover with normal kidney function, sevelamer treatment was associated with reduced osteoclast number and activity leading to improved bone quality. 35 In other studies, when mice were placed on a low-phosphate diet, decreased osteoclast numbers were observed, whereas a high-phosphate diet was associated with enhanced bone resorption. 36,37 Zhang et al demonstrated that in Dmp1 hypophosphatemic knockout mice, a reduction in the number of osteoclasts was observed.…”
Section: Discussionmentioning
confidence: 90%
“…33,34 In the ovariectomized rat model of high turnover with normal kidney function, sevelamer treatment was associated with reduced osteoclast number and activity leading to improved bone quality. 35 In other studies, when mice were placed on a low-phosphate diet, decreased osteoclast numbers were observed, whereas a high-phosphate diet was associated with enhanced bone resorption. 36,37 Zhang et al demonstrated that in Dmp1 hypophosphatemic knockout mice, a reduction in the number of osteoclasts was observed.…”
Section: Discussionmentioning
confidence: 90%
“…Animals' studies had demonstrated that LC and sevelamer have an anabolic effect on bone tissue. 37,38 All meta-analyses are subject to potential bias because of systematic and random errors. 39 Our meta-analysis of randomized controlled trials may have several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of sevelamer on bone volume and strength were seen in a non-CKD model of osteoporosis that involved aged ovariectomized rats (70). Treatment with sevelamer raised the total-body bone mineral density in the femur, tibia, and lumbar spine and also increased the BFR, cortical thickness, and bone volume, resulting in improved bone biomechanical properties.…”
Section: Effects Of Phosphate Binders On Bonementioning
confidence: 97%